Impact of circumpolar deep water on organic carbon isotopes and ice-rafted debris in West Antarctic: a case study in the Amundsen Sea - Lei, Ziyan; Ge, Qian; Chen, Dong; Zhang, Yongcong; Han, Xibin (Frontiers in Marine Science, 2024)
This research delves into the interaction between carbon isotopes, ice-rafted debris (IRD), and Circumpolar Deep Water (CDW) in the Amundsen Sea, West Antarctic. Utilizing sediment core ANT36-A11-04, we traced the source of the organic matter though an analysis of the total organic carbon (TOC), stable carbon isotopes (δ13Corg), and nitrogen content. We identified six environmental events in this region since the Mid-Holocene, which were discerned through a comparative analysis of the δ13Corg, TOC, and IRD content. These events were closely linked to variations in the intensity of the CDW. Notably, the synchronous occurrence of a negative shift in the δ13Corg value and increases in TOC and IRD highlight the significant impact of CDW intrusion, underlining the pivotal role of the CDW in the regional environmental evolution. Specifically, intensified upwelling of the CDW was correlated with increased heat and nutrients, enhanced glacier melting, phytoplankton blooms, higher TOC content, augmented deposition of IRD, and finally resulted in a negative shift in the δ13Corg value. We present a comprehensive picture of the local environmental evolution in the Amundsen Sea, characterized as a marine-glacial-biological coupling model, thereby contributing to a broader understanding of Antarctic environmental dynamics.